PRAKTIKALITAS LKPD MAKROMOLEKUL BERBASIS ETNOSAINS TERINTEGRASI STEAM PADA PEMBELAJARAN KIMIA - Alqhorina, Vivi; Effendi, Effendi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2024)
This study aims to determine the practicality of the macromolecule LKPD (Student Worksheet) Based on ethnoscience integrated STEAM (Science, Technology, Engineering, Arts, and Mathematics) in chemistry learning for class XII SMA. The type of research used in this research is research and development or R&D (Research and Development) with a 4-D development model. The subjects of this study were 2 people chemistry teacher and 23 new students of the Chemistry Department, Faculty of Mathematics and Natural Sciences, Padang State University in 2022. Based on the results of the study, the assessment of the LKPD obtained a practicality value of 92.8% which was included in the very practical category. This study concludes that the Ethnoscience-based STEAM-based macromolecular worksheets in chemistry learning for class XII SMA are included in the practical category and are suitable for use in learning.